2003
DOI: 10.1099/mic.0.26279-0
|View full text |Cite
|
Sign up to set email alerts
|

Different roles for the stress-activated protein kinase pathway in the regulation of trehalose metabolism in Schizosaccharomyces pombe

Abstract: The Wis1p-Sty1p mitogen-activated protein kinase cascade is a major signalling system in the fission yeast Schizosaccharomyces pombe for a wide range of stress responses. It is known that trehalose functions as a protective metabolite to counteract deleterious effects of environmental stresses. Herein it is reported that the expression of genes related to trehalose metabolism in S. pombe, ntp1+ (neutral trehalase) and tps1 + [trehalose-6-phosphate (T6P) synthase], is partially regulated by the Sty1p kinase und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…A S. pombe Datf1 deletion mutant, (atfB is an atf1 homolog), has been reported to be sensitive to osmotic and oxidative stress (Degols and Russell, 1997; Paredes et al, 2003). We therefore examined growth of the DatfB strain on minimal medium agar Fig.…”
Section: Conidia Formation By the Datfb Strain Is Weak On Hyperosmotimentioning
confidence: 99%
See 1 more Smart Citation
“…A S. pombe Datf1 deletion mutant, (atfB is an atf1 homolog), has been reported to be sensitive to osmotic and oxidative stress (Degols and Russell, 1997; Paredes et al, 2003). We therefore examined growth of the DatfB strain on minimal medium agar Fig.…”
Section: Conidia Formation By the Datfb Strain Is Weak On Hyperosmotimentioning
confidence: 99%
“…In both species, ATF/CREB transcription factors play important roles in the expression of osmotic stress-responsive genes that operate downstream of the MAP kinase pathway (Garcia-Gimeno and Struhl, 2000;Takeda et al, 1995). Among the ATF/CREB proteins, S. pombe Atf1 regulates expression of catalase (ctt1) and trehalose-6-phosphate synthase (tps1) under conditions of osmotic and oxidative stress (Degols and Russell, 1997;Paredes et al, 2003). ATF/CREB proteins bind as homodimers or heterodimers to a specific DNA sequence, T(G/ T)ACGT(C/A)A, through a bZIP structural motif, which consists of a leucine zipper that mediates dimerization and an adjacent basic region that binds to DNA (Hai and Curran, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In this organism, two transcription factors, Atf1 and Pcr1, activate gene expressions upon environmental stresses such as oxidative stress or osmotic stress (Takeda et al, 1995;Sanso et al, 2008). Both Atf1 and Pcr1 are included in the ATF/CREB family, a family of bZIP transcription factors, and upregulate many genes, such as the catalase gene ctt1 or the trehalose-6-phosphate synthase gene tps1 (Degols and Russell, 1997;Bell et al, 1998;Paredes et al, 2003). Atf1 and Pcr1 have been shown to bind to the CRE sequence (T[G/T]ACGT[C/A]A) of some target genes by forming a heterodimer with each other (Hai and Curran, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of crosstalking between Sty1p and Pka1p regulates not only glucose repression and oxidative stress response pathways but also trehalose accumulation. Paredes et al (25) reported that the expression of the ntp1 + and tps1 + genes in S. pombe is partially regulated by the Sty1p kinase under salt-induced osmotic stress and conditions of slight oxidative stress and is fully dependent on this kinase under severe oxidative stress. Another study showed that cell viability may depend on capacity to rapidly degrade the trehalose that is accumulated during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Generally in yeast, the regulation of trehalose synthesis and breakdown is done by cAMP-dependent phosphorylation mechanisms (24). It has been reported that the ntp1 + expression is regulated by the pathway of protein kinase cascade activated under osmotic or oxidative stress (23,25) or by the binding of the transcription factors to elements such as cAMP-response element under thermal stress (26). In the present study, ird5 and ird11 were used to evaluate whether or not trehalose contributes to survival under moderate oxidative stress.…”
Section: Introductionmentioning
confidence: 99%